Codicology in Lithuania in 1918-1990: Between Book History and Palaeography - Rima Cicėnienė (Knygotyra)
The article discusses the development of the discipline of codicology in Lithuania in the period 1918-1990 thus continuing the research carried out from the early 19th century until 1918. The concept of codicology and its affiliation with the discipline of book studies allow us to identify the chronology of the research with the development of book studies, which entered the stage of independent science in the period under discussion. This was also the time when the discipline of codicology in Western Europe underwent a quantum leap - with the birth of the term codicology and the emphasis on its distinction from palaeography. The concept expanded to include the study of manuscripts in various aspects - from their physical structure to the reception of written culture. Did this influence the development of the discipline in Lithuania? Did it succeed in renewing the codicological research that had begun at the beginning of the 19th century? How did the science of codicology develop in the turbulent 20th century? Why did codicology failed to become the subject of a separate research and is hardly mentioned in Lithuanian science? The answer to these questions is sought through the bibliographies of Lithuanian book studies and history, publications of sources of the period, and the history of Lithuanian scientific institutions. The research enables us to talk about two distinct periods. Between 1918 and 1939, the subjects of bibliography and book history were formed and established in Lithuanian scholarship, while the history of the manuscript book was recorded as the earliest period of Lithuanian book history. The bibliographies, which were started on a national basis, recorded single copies of codices in a variety of languages and included some external features, but the manuscripts did not receive a closer look. V. Biržiška formulated the concept of the history of the manuscript book with a distinction between the Cyrillic and Latin codices. His insights about the poor quality of manuscript books in the GDL were later developed to some extent but remained mainly unchanged until the 1990s, and apparently influenced the subsequent development of research. The first phase can therefore be called the bibliographical period. The second phase covers the period 1945-1990. The end of the Second World War saw the reactivation of academic institutions, the training of a new generation of historians and librarians, the accumulation of manuscript books, and the appearance of individual works on the history of the book. However, we can only speak of codicological research and attention to the manuscript book as a research object since the 1980s. Historians and philologists (S. Lazutka, E. Gudavičius, V. Raudeliūnas, V. Mažiulis, V. Drotvinas), following the work of the scholars of the Vilnius Imperial University in the early 19th century, began to publish sources of writing. The comprehensive study of the First Statute of Lithuania by S. Lazutka and E. Gudavičius, published in 1983, clearly demonstrated the difference between codicology and palaeography. The detailed codicological description, still called palaeography, was used as an auxiliary research method to argue the origin and originality of the text, the history of its functioning and the dating process. Thus, between 1945 and 1990, codicology completely fulfilled its role as an auxiliary science of history. While book studies became an independent discipline in the period under discussion, codicology did not become as a discipline complete in itself. It remained a discipline between book history and palaeography, looking for a place in the structure of Lithuanian science. Although the term codicology was already in use in the scientific world and the concept of the term had expanded considerably, it did not function in Lithuanian science. However, it is significant to note that the studies in which codicology was used as an auxiliary science at the same time developed the topics of book science, raised new questions, and drew attention to new phenomena and cultural connections.